Identifying personality traits in Oman high schol students: a test for big five-factor model / Muna Saif Abdullah Al-Kalbani - Abdullah Al-Kalbani, Muna Saif (2010)
Using data from 1720 students, a series of three studies validated measure of Big Five personality traits tailored to adolescents. The Adolescent Personal Style Inventory (APSI) (Lounsbury & Gibson, 2006; Lounsbury, Tatum, Gibson, Park, Sundstrom, Hamrick & Wilburn 2003), was used in this study. The instrument has been validated through a scientific method in order to ensure its reliability and validity. Two advanced statistical methods were used in the validation process, namely: Exploratory factor analysis (EFA) and Confirmatory factors analysis (CFA). EFA was used to identify the underlying dimensions of each construct of the instrument. CFA is used to confirm the dimension and to analyze the fitness of the data collected in the hypothesized model. The results show evidence of an accessible indicator of validity and reliability of inventory. The reliability test indicated that the instrument was reliable, given the overall value of Cronbach alpha reliability of .77. The EFA results showed that, the Big Five Personality Inventory Adolescent constructs produced five significant factors. CFA results showed a good fit to study data, where that the goodness-of-Fit indices for the received model were as follows: χ2 =38.903, df = 179, CFI =. 923, GFI = .965, PCOLOSE = 1.00 and RMSEA =. 034, each of the indices was above the threshold values.